2022
DOI: 10.1111/nyas.14781
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure promotes macrophage M1 polarization after Mycobacterium tuberculosis infection via the lncRNA XIST/microRNA–125b–5p/A20/NF–κB axis

Abstract: Experiments have demonstrated the regulation of long noncoding RNA (lncRNA) in tuberculosis (TB), and negative pressure treatment has been associated with the alleviation of TB. Here, we investigated the interaction of negative pressure and the lncRNA X‐inactive specific transcript (XIST) in modulating Mycobacterium tuberculosis (MTB) infection. Initially, we established an in vitro cell model of MTB infection and an in vivo mouse model of MTB infection, followed by treatment with negative pressure. Then, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Luo et al established an in vitro cell model and an in vivo mouse model of Mycobacterium tuberculosis infection and conducted negative pressure treatment. They found that negative pressure treatment after M. tuberculosis infection promoted macrophage polarization to proinflammatory M1 phenotype by regulating the long noncoding RNA XIST/micro-RNA-125b-5p/A20/nuclear factor- κ B axis [ 38 ]. Most transcripts of the human genome sequence are composed of noncoding RNAs, one of which is long noncoding RNA [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luo et al established an in vitro cell model and an in vivo mouse model of Mycobacterium tuberculosis infection and conducted negative pressure treatment. They found that negative pressure treatment after M. tuberculosis infection promoted macrophage polarization to proinflammatory M1 phenotype by regulating the long noncoding RNA XIST/micro-RNA-125b-5p/A20/nuclear factor- κ B axis [ 38 ]. Most transcripts of the human genome sequence are composed of noncoding RNAs, one of which is long noncoding RNA [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results laid a foundation for more direct and in-depth research on the molecular mechanism of long noncoding RNA Gm9866. Some previous studies [20,21,38,[43][44][45] have reported that the nuclear factor-κB family is involved in macrophage polarization. We therefore speculated that long noncoding RNA Gm9866 may act through the nuclear factor-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Two lncRNAs are functionally related to polarized macrophages during MTB infection. For example, Luo et al (27) discovered that XIST expression was upregulated in RAW264.7 cells and human monocyte-derived macrophages (hMDMs) after MTB infection and that its expression was regulated by ESAT-6, an important determinant of MTB virulence. Functionally, XIST serves as a competing endogenous RNA targeting miR-125b-5p, a miRNA that promotes M1 macrophage polarization by modulating A20/NF-kB signalling.…”
Section: Tuberculosismentioning
confidence: 99%
“…A previous study also supported the conclusion that the expression of A20 was upregulated in MTB-infected macrophages, thereby inhibiting the NF-κB pathway and regulating the immune response after MTB infection ( 96 ). The regulatory network of the XIST /miR-125b-5p/A20/NF-κB axis has also been proven to be a molecular mechanism of negative pressure treatment for MTB infection ( 27 ). Another recent study reported that MIR99AHG is upregulated in M2 (IL-4/IL-13)-polarized mouse and human macrophages but downregulated after clinical MTB HN878 strain infection and in PBMCs from active TB patients ( 97 ).…”
Section: Lncrna-based Regulation Of Macrophage Polarization In Infect...mentioning
confidence: 99%
“…Upregulation of lncRNA XIST and downregulation of miR-125b-5p during the infection can be reversed by this treatment strategy. Through modulation of the lncRNA XIST/miR-125b-5p/A20/NF-κB axis, which ultimately increases the activity of NF-κB p65, this regimen facilitates the polarization of macrophages to the M1 phenotype, enhancing the inflammatory response to reduce M. tuberculosis survival ( 162 ).…”
Section: The Role Of Lncrnas In Immune Regulation In Tuberculosismentioning
confidence: 99%